Touchscreen generation: children's current media use, parental supervision methods and attitudes towards contemporary media. (20th January 2017) - Kostyrka‐Allchorne, Katarzyna; Cooper, Nicholas R.; Simpson, Andrew
Abstract: Aim: To explore media preferences and use among young children, as well as to obtain information about parental supervision methods and beliefs about media. Method: Ninety parents of three‐ to six‐year‐olds, recruited from a relatively economically advantaged area in the United Kingdom, completed a media opinion survey. Results: Although traditional television remains the favourite type of media platform among young children, touchscreen devices are gaining in popularity, and may promote simultaneous multi‐screen use. Moreover, parents believe that the effects of media on developmental outcomes are generally positive. However, they do monitor the content of traditional and new media their children are exposed to. Conclusion: This study shows an emerging evidence of concurrent multi‐screen use among very young children. More detailed examination of early media multitasking, and its relationship to cognitive and behavioural outcomes, is necessary.